Predicting Aerobic Fitness Improvements after Participation in a Hybrid Supervised and Home-Based Exercise Program in People with Type 2 Diabetes - Yang, Pearl; Oh, Paul (Canadian journal of diabetes, 2013)
Structured, gym-based exercise training has been shown to be effective at improving aerobic fitness and glycemic control in persons with type 2 diabetes. However, community-based diabetes programs more commonly incorporate less structured programming, promoting exercise at home. The objectives of this study were to evaluate a community-based, hybrid exercise program encouraging home-based exercise for improving aerobic fitness, and to examine the components of exercise prescription that contribute to this fitness change. A retrospective analysis of 583 persons with type 2 diabetes who had participated in the Toronto Rehabilitation Institute's diabetes exercise program was performed. All subjects completed 6 months of structured aerobic and resistance exercise supervised once per week on-site, with 4 more unsupervised sessions per week completed at home. Cardiopulmonary fitness testing and anthropometric measures were performed at baseline and at program completion. A multivariate regression analysis examined the outcome of aerobic fitness (peak oxygen consumption), controlling for age, sex, body mass index, weight change, initial fitness at entry into the program and walking exercise performed (distance, duration and pace). Peak oxygen consumption improved significantly from 19.1±0.2 at baseline to 21.9±0.3 mL·kg−1·min−1 at 6 months (p<0.001). Weight and body mass index also improved significantly (p<0.001). The regression model was able to predict 76.9% of the variance in aerobic fitness, with distance walked contributing the most to improved exercise capacity. A 6-month hybrid exercise program delivered in a community rehabilitation program setting successfully improved aerobic fitness in people living with type 2 diabetes. L’entraînement structuré en gymnase s’est révélé efficace pour améliorer la condition physique aérobie et la régulation de la glycémie chez les personnes ayant le diabète de type 2. Cependant, les programmes communautaires pour les diabétiques incorporent plus fréquemment des programmes moins structurés, qui favorisent l’exercice à la maison. Les objectifs de cette étude étaient d’évaluer un programme d’exercices communautaire hybride encourageant l’exercice à la maison pour améliorer la condition physique aérobie et pour examiner les composantes de la prescription d’exercices qui contribuent à cette modification de la condition physique. Une analyse rétrospective composée de 583 personnes ayant le diabète de type 2 qui avaient participé au programme d’exercices conçu pour les diabétiques du Toronto Rehabilitation Institute a été réalisée. Tous les sujets ont réalisé 6 mois d’exercices structurés aérobiques et contre résistance supervisés une fois par semaine sur le site et 4 séances non supervisées par semaine réalisées à la maison. L’épreuve d’effort pour évaluer la forme cardiopulmonaire et les mesures anthropométriques ont été réalisées au début et à la fin du programme. Une régression multivariable a examiné l’évolution de la condition physique aérobie (consommation maximale d’oxygène) en tenant compte de l’âge, du sexe, de l’indice de masse corporelle, du changement de poids, de la condition physique au début du programme et de l’exercice de marche réalisé (distance, durée et cadence). La consommation maximale d’oxygène s’est significativement améliorée de 19,1 ± 0,2 au début à 21,9 ± 0,3 ml kg-1·min-1 à 6 mois (p < 0,001). Le poids et l’indice de masse corporelle se sont également significativement améliorés (p < 0,001). Le modèle de régression a été capable de prédire 76,9 % de la variance de la condition physique aérobie par la distance de marche parcourue contribuant le plus à l’amélioration de la capacité à faire de l’exercice. Un programme hybride d’exercices de 6 mois offert dans le cadre d’un programme de réadaptation communautaire a amélioré avec succès la condition physique aérobie des personnes vivant avec le diabète de type 2.